168 A novel prostate-restricted tumor-associated antigen: a potential therapeutic target. (10th December 2020) - Lopez Bujanda, Zoila (Areli); Obradovic, Aleksandar; Nirschl, Thomas; O'Donnell, Timothy; Laserson, Uri; Macedo-Gonzales, Rodney; Reshef, Ran; Yuan, Tiezheng; Soni, Mithil; Antonarakis, Emmanuel; Larman, Benjamin; Muranski, Pawel; et al.
Abstract : Background: Prostate cancer is the second leading cause of cancer related death in men in the United States, mainly due to disease progression to metastatic castration-resistant prostate cancer (mCRPC). Although immunological treatment with the FDA-approved vaccine sipuleucel-T extends survival for 2–4 months by targeting the prostate-restricted antigen PAP, the identification of more immunogenic tumor-associated antigens (TAAs) continues to be an unmet need. Methods: We evaluated the differential expression profile of the subset of epithelial cells reported to give rise to CRPC from mice following an androgen deprivation/repletion cycle. The expression levels of a set of androgen-responsive genes was further evaluated in prostate, brain, colon, liver, lung, and skin normal tissues from murine and human databases. The expression of a novel prostate-restricted TAA was then analyzed in primary tumors across all human cancer types in The Cancer Genome Atlas (TCGA). Finally, the immunogenicity of this novel prostate-restricted TAA was evaluated in vitro by autologous co-culture assays with cells from healthy donors and in vivo by antibody profiling (PhIP-Seq) in the sera of a cohort of prostate cancer patients treated with AR blockade alone or in combination with the cell-based vaccine GVAX. Results: Here, we discovered a set of androgen-responsive genes exclusively expressed by the putative cell-of-origin for prostate cancer. We confirmed prostate-restricted enrichment of these androgen-responsive genes in normal tissues from murine and human databases. Among these prostate-restricted genes, we identified PAP, PSA, and a novel non-mutated TAA. This novel TAA was confirmed to be expressed in prostate cancer. Furthermore, its expression was associated with survival in patients with primary prostate cancer. Interestingly, we found that pro-inflammatory activated TBET+ EM CD8 and CD4 T cells were expanded by moDCs pulsed with our novel TAA to a greater extent than moDCs pulsed with either PAP or PSA were used. An IgG antibody response to this novel TAA was detected in 30% of vaccinated patients, while fewer than 8% of vaccinated patients developed antibody responses to PSA or PSMA. Conclusions: Taken together, these results suggest we have found a novel immunogenic prostate-restricted TAA that represents a promising therapeutic target for treating mCRPC.